Kontribusi Hasil Hutan Bukan Kayu dari Hutan Produksi Terbatas bagi Pendapatan Rumah Tangga Masyarakat - Rudi Meirawan Pohan; Agus Purwoko; Tri Martial (Program studi Kehutanan USU, 2014)
Forest area is still gives contribution from non timber forest products (HHBK) economic value to household income of the community around the forest higly. This research was conducted on June-July 2013 in Simasom Village, Subdistrict of Padangsidimpuan Angkola Julu, Padangsidimpuan City by using purposive sampling method which means that the choised respondents were who employing at non timber forest products (HHBK) directly from limited production forest. The aims of this research were to identify the kinds of HHBK, tho determine the economic value of HHBK along with the contributions to household income, and to determine the income distribution of this HHBK employing and to make a poverty analysis about the people concerned on this HHBK income to reduction of the people’s poverty rate. The results of this research showed that the kinds of HHBK which is employed by the people from limited production forest are: rattan, nira water, palm fiber, sugar from palm sugar, fruits of sugar palm, bamboo, cinnamons, deer, bracken, pig, durian, candlenut, petai, lanseh fruit, top soil, and firewood. While, the total contribution of HHBK from limited production forest to household income in Simasom Village was Rp. 723.519.000,-/year (39,22%). Then, the imbalance of people’s income distribution from HHBK employment from limited production forest can be measured according to Gini Coefficient value that is 0,42 which means that the high enough imbalance between the rich employer and the poor one has happened. While, the income from HHBK has been contributed to reduce the persistent poverty people about 15 persons or about 30% of household.Key Words: Non timber forest products, economic value, contribution of income, income distribution, poverty.